PERFORMANCE ANALYSIS OF WASTE GATE VALVE IN REGULATING EXhaust GAS FLOW TOWARDS THE TURBOCHARGER FOR THE FLEXIBLE COMBUSTION PROCESS ON THE TANGGUH JAYA LNG/C SHIP - Ala, Asman; Zakiah, Diah; Fadly, Faisal (Dinasti International Journal of Digital Business Management, 2021)
A turbocharger is an auxiliary engine that functions to supply air into the cylinder and in general every turbocharger has two sides, namely, the compressor side and the turbine side, the rotation of the turbocharger is generated from the remaining exhaust gases from combustion in the cylinder which goes to the turbine side of the turbocharger and produces rotation. on that side and also rotates at the same speed on the compressor side of the turbocharger. The amount of air that will enter the cylinder depends on the rotation of the turbocharger itself, if the rotation of the turbocharger is too fast it will produce too much air in the cylinder which results in knocking or knocking on the main drive engine, whereas if the turbocharger rotates too slowly it will result in too little quantity of air resulting in a misfire or failure of combustion in the cylinder. To determine the rotational speed of the turbocharger, we need a tool that can regulate the quantity of the remaining exhaust gases from combustion in the cylinder, namely the waste gate valve. When the writer carried out the sea practice, the writer experienced various interesting things about the waste gate valve, such as the opening that did not match the degree of the waste gate valve to the difference in the indicator readings on the waste gate valve. In this case the author will analyze the cause of the imperfect supply of air entering the cylinder caused by the non-optimal performance of the waste gate valve.